A conceptual analysis of psychopathy. - Van Onselen, Mathew (My University, 2010)
In this paper I conduct a conceptual analysis of the personality disorder known as “psychopathy.” The concept has its roots in psychology, but in recent years there has been much investigation into the nature of psychopathy in both philosophy and neuroscience. These three disciplines frequently work independently of one another, and it is my aim to provide a single account of psychopathy that is informed from all three disciplines, using philosophical analysis as a means to elucidate key aspects of the disorder. Apart from exploring the aspects of psychopathic wrongdoing, emotions, and practical rationality, I also explore the understanding of psychopaths as “morally insane,” and conclude that the concept of psychopathy is best understood from a nonmoral point of view.